Eco-industrial transformation in Uganda: performance evaluation of industrial parks using the international EIP framework - Negesa, Doryn; Geme, Tom; Nijman-Ross, Elke; Ntawuhiganayo, Elisée Bahati (Frontiers in Sustainability, 2023)
This study investigates the transformation of traditional industrial parks into Eco-Industrial Parks within Uganda, with a focus on the Kampala Industrial and Business Park and the Mbale Industrial Park. Utilizing the International Framework for Eco-Industrial Parks as a guiding tool, the research evaluates the parks' alignment with global eco-industrial park standards. Eco-industrial parks, serving as catalysts for industrial ecology development, promote sustainable practices, resource optimization, and symbiotic inter-industrial relationships. The analysis underscores the pivotal roles of various stakeholders, including the government, enterprises, international cooperators, financial institutions, local communities, and educational and research entities. While Uganda has shown commitment in policy formulation towards industrial transformation, the practical realization of eco-industrial parks remains in its early stages. Challenges such as waste management, energy supply, and community engagement are evident. However, the potential for eco-industrial park development is promising, especially with enhanced international cooperation, financial backing, and community involvement. The study concludes by emphasizing the need for region-specific indicators, tailored educational initiatives, and the selection of Mbale as a pilot city for eco-industrial park development, setting a precedent for the country's sustainable industrial trajectory.